A systematic review of lay views about infant size and growth. Issue 2 (11th August 2006) - Lucas, P; Arai, L; Baird, J; Kleijnen, J; Law, C; Roberts, H
Abstract : Objectives: To understand lay views on infant size and growth and their implications for a British population. Methods: A systematic review of parental and other lay views about the meanings and importance of infant size and growth using Medline, PsycInfo, CINAHL, Sociological Abstracts, IBSS, ASSIA, British Nursing Index ChildData, Caredata, SIGLE, Dissertation Abstracts (US), Index to Theses. 19 studies, most of which reported the views of mothers, from the US, Canada, the UK and Finland were reviewed. Results: Notions of healthy size and growth were dominated by the concept of normality. Participants created norms by assessing and comparing size and growth against several reference points. When size or growth differed from these norms, explanations were sought for factors that would account for this difference. When no plausible explanation could be found, growth or size became a worry for parents. Conclusions: Parents consider the importance of contextual factors when judging what is appropriate or healthy growth. For public health advice to be effective, lay, as well as scientific, findings and values need to be considered.